Comparative efficacy assessment of solitary SMD beaded ultraviolet-C light emitting diodes for enhanced disinfection of high-touch surfaces - Jahanzeb Sheikh,; Tan, Tian Swee; Syafiqah Saidin,; Azli Yahya,; Sameen Ahmed Malik,; Chua, Lee Suan; Serrano, Jose Javier; Tiong, Matthias Foh Thye; Leong, Kah Meng; Jawad Shafique, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Ultraviolet (UV) light-emitting diodes (LED) have gained attention for substituting conventional disinfection methods due to efficiency, environmental benefits, and safety since the early 2000s. Earlier research has investigated high-power UV-disinfection systems employing UV tubes for effectively disinfecting surfaces. However, such systems come with several limitations, including the delicacy of UV tubes, the mercury component, and the larger size of the equipment, requiring trained professionals for handling. Additionally, owing to their larger size, these systems are unable to adequately treat shaded spaces, resulting in insufficient disinfection. Therefore, this study aimed to investigate and compare the efficacy of surface mount device (SMD)-beaded UV-C LEDs against Staphylococcus aureus (S. aureus) bacterium to elucidate the self-reliant disinfection capacity, focusing on achieving peak disinfection efficiency up to 15 cm for treating high-touch regions. Under maximum exposure settings (15 cm, 60 s), a considerable reduction of 1.7-log10 inactivation was achieved with KW6565 upon exposure to 0.054 mJ-cm-², corresponding to an efficiency of 98%. This swift decline led to a reduction in bacterial concentration from the initial level to 1.00x108 CFU/mL. However, the RZX variant necessitated the dose of 0.018 mJ-cm-² to achieve a 1.6-log10 inactivation or 97.6% percent reduction under similar exposure settings. The efficacy of both the 4W variants were notably impacted by the UV dose (p<0.05) at different distances, compared to the control group, revealing a positive correlation with the bactericidal rate. To conclude, this research substantiated the potential of a 4W UV-LED to establish an enhanced disinfection strategy, particularly for treating shady spaces.